Innovation in oncology clinical trial design. (March 2019) - ,; Hanauske,; Wacheck, V.; Collignon, O.; Bruzzi, P.; Gross, J.; Riehl, T.; Bretz, F.; Dollins,; Radtke, I.; Verweij, J.; Hendriks, H.R.; et al.
Highlights: Standard Phase III trials are not always suited to assess new targeted oncology drugs. Innovative trial designs and alternative regulatory pathways are therefore needed. Enabling patients earlier potential benefit from rapid access to these novel drugs. Abstract: Progress in and better understanding of cancer biology causes a shift in cancer drug development: away from the evaluation of drugs in large tumour histology defined patient populations towards targeted agents in increasingly heterogeneous molecularly defined subpopulations. This requires novel approaches in clinical trial design by academia and industry, and development of new assessment tools by regulatory authorities. Pharmaceutical industry is developing new targeted agents generating many clinical studies, including target combinations. This requires improved operational efficiency by development of innovative trial designs, strategies for early-stage decision making and early selection of candidate drugs with a high likelihood of success. In addition, patient awareness and ethical considerations necessitate that agents will be rapidly available to patients. Regulatory Authorities such as the European Medicine Agency and national agencies recognise that these changes require a different attitude towards benefit-risk analysis for drug approval. The gold standard of randomised confirmatory Phase III trials is not always ethical or feasible when developing drugs for treatment of small cancer populations. Alternative strategies comprise accelerated approval via conditional marketing approval, which can be granted in the EU based on small non-randomised Phase II trials. The paper describes innovative trial designs with their pros and cons and efforts of pharmaceutical industry and regulatory authorities to deal with the paradigm shift. Furthermore, all stakeholders should continue to share their experiences and discuss problems in order to understand the position and concerns of the other stakeholders to learn from each other and to progress the field of novel oncology clinical trial design.